Formative research on accreditation models of the university programs in Peru - Esteban Rivera, Edwin Roger; Piñero Martín, María Lourdes; Rojas Cotrina, Amancio Ricardo; Callupe Becerra, Sonia Fiorella; Jacha Ayala, Zósimo Pedro (Journal of the University of Zulia, 2021)
Society requires universities to comply with their guiding principles, including the development of research; hence there is no university accreditation model that omits the training of researchers. The present work aims to analyze how formative research is approached in the quality models of the Peruvian university system, through a bibliographic review, to improve the human talent produced by the educational system. In the past, Peru established two quality models for the accreditation of professional careers, the first entered into force in 2009 and explicitly mentions formative research, in addition, it provides guidelines on how it should be developed in the programs; the second, in force since 2016, addresses it implicitly. Both models consider that the teaching and learning process must be articulated with research, technological development, innovation and social responsibility, in order to guarantee the comprehensive training of students.